A Design of Ammonia Concentration Monitoring System Using Radio Communication - Asmoro, Renetha Salma Myesha; Wardoyo, Arinto Yudi Ponco; Anggraeni, Dewi; Pramundhitya, Maria; Widhowati, Azarine Aisyah; Adi, Eko Teguh Purwito (Master Program in Mechanical Engineering, Gunadarma University, 2024)
The adverse effects of air pollution on human health, climate change, and ecosystems have made air pollution a major problem in the last four years. Ammonia is a pollutant that has an impact on human health. This study aims to develop a monitoring system for NH3 concentrations using radio communication. The radio module used in data communication is SX1278. The sensor used in this system is MICS-6814, which is integrated with Arduino Nano. The sensor used has been tested and can be used in emission detection. Monitoring results data is displayed on the LCD and serial monitor. Data communication performance for the monitoring process was tested at various distances. This system can reach a measurement distance of 80 meters, with the best distance used for monitoring being less than 50 meters. This system was tested to be able to monitor a different level building. The result shows that the system's performance is the RSSI at a distance of 0 meters is -28 dBm. At the same time, the farthest distance of 80 meters is -101 dBm. The data transmission has a delay time of 1,300 ms and an accuracy of 91%. The ambient NH3 concentration in the area of Malang is found in the range of 0.001 ppm.